Modelling of Solar Cell Junction Temperature for Crystalline Silicon Photovoltaic Module - Chen, Zewen; Yang, Yuehua; Niu, Haibo; Zhu, Youzhang; Xu, Xixiang; Yu, Mingzhe; Yang, Hong (SiliconPV Conference Proceedings, 2026)
Determination of the junction temperature of solar cells is critical for accurately evaluating on-site performance of solar modules. It is difficult to acquire the junction temperature of cells because solar cells are laminated and encapsulated in modules. In this paper, a fine steady-state thermal model is established to directly obtain the junction temperature of cells in the field. The model only needs plane of array (POA) irradiance, backsheet temperature, ambient temperature and wind speed. The junction temperature of the cells obtained from the model is validated by the equivalent cell temperature method in IEC 60904:2021. The results indicate that the model works well in the POA irradiance range of 400-800 W/m2. In addition, the effect of POA irradiance, ambient temperature on temperature difference between junction temperature and backsheet temperature were investigated. It is found that the temperature difference between junction temperature and backsheet temperature is increased with increasing POA irradiance. The required time of modules to reach the thermoequilibrium state is affected by the ambient temperature. The obtained results in this paper provide useful insights into performance evaluation and power generation forecasting of solar modules.